2020
DOI: 10.1029/2020ja028225
|View full text |Cite
|
Sign up to set email alerts
|

Six‐Day Periodic Variation in Equatorial Ionization Anomaly Region

Abstract: Using the location of equatorial ionization anomaly (EIA) crest derived from GPS observations and CHAllenging Minisatellite Payload (CHAMP) satellite measurement, along with the F2 layer peak height (hmF2), critical frequency (foF2), and the equatorial electrojet (EEJ) in India and China longitudinal sectors, we found the obvious 6-day oscillation in these ionospheric parameters during 16 April to 31 May 2003 and 21 September to 26 October 2004. The tidal amplitudes of EEJ are enhanced during the positive phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Longitudinal differences in the equatorial ionization anomaly (EIA) are a source of information about spatial differences in the processes that influence their creation and decay. Changes in their radiance have often been linked to differences in the equatorial electrojet (EEJ) strength which are attributable to longitudinal differences in solar tidal forcing (England et al., 2006; Fang et al., 2009; Jin et al., 2008; Lühr & Manoj, 2013; Mo & Zhang, 2020; Pedatella et al., 2012; Venkatesh et al., 2015; Yamazaki & Maute, 2016; Zhou et al., 2016). Variations in the optical dayglow radiances at the northern crest's latitudes over Indian longitudes show a similar relationship with the EEJ strength (Karan et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal differences in the equatorial ionization anomaly (EIA) are a source of information about spatial differences in the processes that influence their creation and decay. Changes in their radiance have often been linked to differences in the equatorial electrojet (EEJ) strength which are attributable to longitudinal differences in solar tidal forcing (England et al., 2006; Fang et al., 2009; Jin et al., 2008; Lühr & Manoj, 2013; Mo & Zhang, 2020; Pedatella et al., 2012; Venkatesh et al., 2015; Yamazaki & Maute, 2016; Zhou et al., 2016). Variations in the optical dayglow radiances at the northern crest's latitudes over Indian longitudes show a similar relationship with the EEJ strength (Karan et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although the increase of polar stratospheric temperature is large during the SSW event in 2012, the wave power at the 14-15 day period is particularly low during this event, which may be due to a small decrease of the polar stratospheric zonal wind (Tang et al, 2020). Mo and Zhang (2020) showed that the temporal extent of wave power at 14-15 day period is consistent with the temporal extent of the decrease of the stratospheric zonal mean wind rather than the increase of stratospheric temperature during SSW. Besides NH winter, this 14-15 day period also occurs in other Obviously, the 14.76-day periodic component is related to M2 with the 12.42-hr period (Yamazaki et al, 2012).…”
Section: Results and Analysismentioning
confidence: 65%
“…Furthermore, a quasi-6 days oscillation is evident in the northern crest during DoY 253-273, but is very weak in the southern crest. The weaker 6-day amplitude in the southern EIA crest was also noticed in the Antarctica SSW in year 2002 (Mo and Zhang, 2020), and was likely related to meridional wind that can cause hemispheric asymmetry in TEC.…”
Section: Resultsmentioning
confidence: 78%